2019
DOI: 10.1253/circj.cj-19-0872
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Toxin–Targeting as a Therapeutic Strategy for Preventing Cardiorenal Syndrome

Abstract: Chronic kidney disease (CKD) is a global health problem. CKD patients are at high risk of developing cardiovascular disease (CVD), including coronary artery disease, heart failure and stroke. Several factors invoke a vicious cycle of CKD and CVD, which is referred as to "cardiorenal syndrome". Among these factors, the compounds retained through loss of renal excretion play a pathological role in causing atherosclerosis and CVD. These compounds have been broadly classified as uremic toxins because of their accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…The role of uremic toxins in the development of cardiac remodeling is less well established. Recent work sheds light on the potential roles of asymmetric dimethylarginine (ADMA), advanced glycation end-products (AGE), trimethylamine N-oxide (TMAO) and indoxyl sulfate [69]. ADMA has been reported to be involved in regulation of nitric oxide, reactive oxygen species and renal anemia [69,70].…”
Section: Uremic Toxinsmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of uremic toxins in the development of cardiac remodeling is less well established. Recent work sheds light on the potential roles of asymmetric dimethylarginine (ADMA), advanced glycation end-products (AGE), trimethylamine N-oxide (TMAO) and indoxyl sulfate [69]. ADMA has been reported to be involved in regulation of nitric oxide, reactive oxygen species and renal anemia [69,70].…”
Section: Uremic Toxinsmentioning
confidence: 99%
“…Recent work sheds light on the potential roles of asymmetric dimethylarginine (ADMA), advanced glycation end-products (AGE), trimethylamine N-oxide (TMAO) and indoxyl sulfate [69]. ADMA has been reported to be involved in regulation of nitric oxide, reactive oxygen species and renal anemia [69,70]. The AGE/RAGE axis is responsible for cell damage in CVD [69], driving cardiac fibrosis.…”
Section: Uremic Toxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atherosclerosis, autoimmune disease, diabetes mellitus, and inflammatory diseases are closely linked to the AGE receptor-ligand axis [ 121 , 122 , 123 , 124 ]. AGEs induce cell injury by interacting with their receptor, denominated receptor for advanced glycation end products (RAGE), which is a ubiquitous multiligand transmembrane cell surface receptor of the immunoglobulin superfamily [ 116 , 125 , 126 , 127 ]. We also previously demonstrated that AGEs induced RAGE expression in endothelial cells [ 128 ].…”
Section: Transporters and Receptors Of Uremic Toxins In The Endothmentioning
confidence: 99%